Immune Reconstitution in Late-Presenting HIV-Positive a Case with Idiopathic Liver Cirrhosis and Ischemic Brain Stroke - Ivaylo Pakov (Journal of Biomedical & Clinical Research)
A patient diagnosed with late-presenting HIV infection [CD4 count 86 cells/mm3, viral load (VL) 95 000 copies RNA/mL], treated with DRV/c 800/150 mg (Rezolsta®) and TDF/FTC 200/245 mg, was hospitalized with ischemic brain stroke, confirmed by CT scan and MRI. Motor functions quickly recovered, but nausea, abdominal heaviness, ascites, and hepatosplenomegaly appeared. Laboratory investigations revealed anaemia, thrombocytopenia, normal transaminases, increased GGT and negative serological tests for HBV and HCV and she was diagnosed with Gastroenterologists diagnosed liver cirrhosis. After 20 days of hospital treatment, the patient recovered from the stroke and ascites but with persisting anaemia and thrombocytopenia. Liver cirrhosis had been confirmed, and relevant treatment had been administered. Six months later, an MRI of the brain revealed an improved image. Follow-up showed stabilized somatic and neurologic status, improved laboratory parameters, stable T-helper count and undetectable viral load (VL). ART regimen continued with Raltegravir 400 mg (Isentress®) 2×1 tablet/24 h, TDF/FTC 200/245 mg 1 tablet/24 h. Three months later, the patient continued her treatment continued abroad. The increased access to precise diagnosis and treatment with improved adherence has transformed the HIV-infection into a manageable chronic health condition, even in complicated cases.